Traditional vs technology: a case study on teaching methodology / Tg Suhaila Mohd Yusof @ Rasid - Mohd Yusof @ Rasid, Tg Suhaila (2011)
This study focus on the teachers’ preference on the use of teaching aids: traditional vs technology teaching aids. The sample for this study involved the teachers from secondary schools. The respondents chosen were English teachers from two rural schools which are Sekolah Menengah Kebangsaan Bukit Katil and Sekolah Menengah Kebangsaan Kelebang Besar and two urban schools which are Sekolah Menengah Kebangsaan Tun Tuah and Sekolah Menengah Kebangsaan Durian Daun. A set of questionnaire consists of five sections had been distributed to collect the data from the teachers’ view and preference on the items related. The findings showed that there are different perception and preference on the use of teaching aids among teachers in urban and rural schools. This study also revealed that there are some areas that the teachers aware and are not aware on the uses and advantages of teaching aids in teaching especially in ESL subject. Thus, the less elements and focus on technology skills among the teachers should be given priority and consideration in order to ensure the teachers have enough knowledge to teach the students using the technology methods. The outcomes of this study would benefit most the teachers especially ESL teachers who are involved in this study. In addition, other organizations and related groups could also benefit from this study for the future planning and implementation of the activities and curriculum in the teaching and learning process for English language. The use of teaching aids will give benefits to teachers and students and the creativity can be gain through it.